The case for small-scale, community-integrated, therapeutic facilities: Utility and feasibility for policy transfer to the Victorian youth justice system - Oostermeijer, Sanne (Journal of criminology, 2024)
Several jurisdictions around the world have recognised that meaningful youth justice reform is more likely to be achieved when moving away from the reliance on large-scale conventional youth justice detention institutions. Small-scale, community-integrated, therapeutic facilities (referred to as “community-integrated facilities”) are more likely to provide an opportunity to facilitate systemic reforms that are necessary to improve outcomes for justice-involved young people, reduce institutional violence, and ultimately improve public safety. Based on recent reforms in the Netherlands, this article aims to describe the potential benefits and feasibility of implementing community-integrated facilities with a specific focus on Victoria, Australia. We will do so by considering the key operational elements and facilitators to implementation as identified previously in an evaluation of the Dutch reforms. While this article involves a single specific context, as a case study it may nevertheless illuminate implications for other jurisdictions considering similar policy transfer activities.